Maurieseuma, a new genus to accommodate Hylebainosoma nontronense Mauriès & Kime, 1999, and the revalidation of the genus Romanosoma Mauriès, 2015 (Diplopoda: Chordeumatida: Haaseidae) - Antić, Dragan; Spelda, Jörg (Zootaxa, 2022)
A new genus, Maurieseuma gen. nov., is established to accommodate the species Hylebainosoma nontronense Mauriès & Kime, 1999. As result, the following new combination is proposed: Maurieseuma nontronense (Mauriès & Kime, 1999) comb. nov. The new genus is diagnosed and briefly described with some new details missing in the previous two descriptions of the species accommodated in it. In addition, we consider Romanosoma Mauriès, 2015 as a valid genus, leaving Hylebainosoma Verhoeff, 1899 with two species. The similarities and differences between the genera Maurieseuma gen. nov. and Romanosoma, as well as with the remaining three genera of Haaseidae are briefly discussed. An identification key is given to all five genera of the family Haaseidae.